Endoscopic ultrasound-guided gallbladder drainage as a rescue therapy for unresectable malignant biliary obstruction: a multicenter experience - Issa, Danny; Irani, Shayan; Law, Ryan; Shah, Shawn; Bhalla, Sean; Mahadev, Srihari; Hajifathalian, Kaveh; Sampath, Kartik; Mukewar, Saurabh; Carr-Locke, David L.; Khashab, Mouen A.; Sharaiha, Reem Z. (Endoscopy, 2020)
Background Endoscopic retrograde cholangiopancreatography (ERCP) is often unsuccessful in patients with duodenal stenosis or malignant ampullary infiltration. While endoscopic ultrasound-guided biliary drainage (EUS-BD) has been proposed as an alternative, EUS-guided gallbladder drainage (EUS-GBD) is an attractive option when both approaches fail. We aimed to assess the effectiveness and safety of EUS-GBD as rescue therapy for malignant distal bile duct obstruction. Methods A multicenter retrospective study was performed on patients with unresectable malignant distal bile duct obstruction who underwent EUS-GBD between 2014 and 2019 after unsuccessful ERCP and EUS-BD. Clinical success was defined as a decrease in serum bilirubin of > 50 % within 2 weeks. Results 28 patients were included, with a lumen-apposing metal stent used in 26 (93 %) and a self-expandable metal stent in two (7 %). The technical success rate was 100 %. The clinical success rate was 93 %, with an improvement in bilirubin (7.3 [SD 5.4] pre-procedure vs. 2.8 [SD 1.1] post-procedure; P = 0.001). Delayed adverse events included food impaction of the stent (n = 3), with a further two patients developing cholecystitis and bleeding. Conclusion This study demonstrates the feasibility of gallbladder drainage to relieve malignant distal bile duct obstruction in patients with failed ERCP and EUS-BD.